Steroid receptor coactivators in Treg and Th17 cell biology and function - Gilad, Yosi; Shimon, Ortal; Han, Sang Jun; Lonard, David M.; O’Malley, Bert W. (Frontiers in Immunology, 2024)
Steroid receptor coactivators (SRCs) are master regulators of transcription that play key roles in human physiology and pathology. SRCs are particularly important for the regulation of the immune system with major roles in lymphocyte fate determination and function, macrophage activity, regulation of nuclear factor κB (NF-κB) transcriptional activity and other immune system biology. The three members of the p160 SRC family comprise a network of immuno-regulators that can function independently or act in synergy with each other, and compensate for -or moderate -the activity of other SRCs. Recent evidence indicates that the SRCs are key participants in governing numerous aspects of CD4 + T cell biology. Here we review findings that establish the SRCs as essential regulators of regulatory T cells (Tregs) and T helper 17 (Th17) cells, with a focus on their crucial roles in Treg immunity in cancer and Treg-Th17 cell phenotypic plasticity.